(untitled) (Journal of Hama University, 2022)
The aim of the research is to study the impact of social engagement on the consumer’s emotion for social media sites of consumers of ready-made clothing brands in the Syrian market. The descriptive approach was adopted, an electronic questionnaire was designed, and published in the virtual Facebook community; Where 224 valid responses for the analysis were obtained from a sample of consumers (actual and potential) for the ready-made clothes market in Syria. The most important findings of this research were that there is a very weak relationship between the rates of repeat visits to the studied sites and both emotional contagion and social comparison. It was attributed to neglecting the role of these elements, and not investing them optimally by the studied companies. A correlative relationship has also emerged between the duration of the visit to these sites and each of the emotional contagion and social comparison, and therefore it is necessary to invest in the field of marketing through social media sites using all available tools and elements because of their impact on the consumer and his purchasing decisions.